Pre-service teachers' efficacy beliefs and emotional states. Issue 1 (2nd January 2016) - DeMauro, Anthony A.; Jennings, Patricia A.
Abstract : Teachers' efficacy beliefs play an important role in how they create quality learning environments. When pre-service teachers (also known as initial teacher trainees) develop strong efficacy beliefs, they can be confident in their abilities to be successful teachers once they enter the field. One way pre-service teachers obtain efficacy information is through their emotional states. Positive emotional experiences like joy and satisfaction may enhance a teacher's sense of efficacy, while undesirable emotions such as fear and worry could be debilitating to efficacy beliefs. The current study investigated how feelings of depression, anxiety, and stress contributed to efficacy beliefs among a sample of 297 American pre-service teachers. Results from regression analysis showed that depressive symptoms negatively predicted teacher efficacy beliefs. However, reports of anxiety and stress did not significantly predict efficacy. Student teaching experience also did not significantly predict teacher efficacy.